Modelling a Coupled Thermoelectromechanical Behaviour of Contact Elements via Fractal Surfaces - G. Mazzucco; F. Moro; M. Guarnieri (Modelling and Simulation in Engineering)
A three-dimensional coupled thermoelectromechanical model for electrical connectors is here proposed to evaluate local stress and temperature distributions around the contact area of electric connectors under different applied loads. A micromechanical numerical model has been developed by merging together the contact theory approach, which makes use of the so-called roughness parameters obtained from experimental measurements on real contact surfaces, with the topology description of the rough surface via the theory of fractal geometry. Particularly, the variation of asperities has been evaluated via the Weierstrass-Mandelbrot function. In this way the micromechanical model allowed for an upgraded contact algorithm in terms of effective contact area and thermal and electrical contact conductivities. Such an algorithm is subsequently implemented to construct a global model for performing transient thermoelectromechanical analyses without the need of simulating roughness asperities of contact surfaces, so reducing the computational cost. A comparison between numerical and analytical results shows that the adopted procedure is suitable to simulate the transient thermoelectromechanical response of electric connectors.